Pathogenesis and Treatment of Chronic Pruritus - Kwatra, Shawn G. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Edition Issue on the "Pathogenesis and Treatment of Chronic Pruritus" contains an overview of various known causes of chronic pruritus and emerging therapeutics. Chronic pruritus is an itch that lasts longer than six weeks, and is associated with a variety of dermatologic, systemic, neurologic, and psychiatric etiologies. Itch negatively impacts patient quality of life, and has devastating psychosocial consequences. The manuscripts published in this Special Issue are also a showcase of the current understanding of the pathogenesis of chronic pruritus, along with its epidemiology, diagnostic workup, and therapeutic approaches used to treat chronic pruritus. A special focus is also placed on prurigo nodularis, a severely pruritic chronic inflammatory skin disease.